High reversible cycling performance of carbon dioxide electrolysis by flat-tube solid oxide cell. (15th May 2022) - Li, Chaolei; Wu, Anqi; Xi, Chengqiao; Guan, Wanbing; Chen, Liang; Singhal, Subhash C.
Highlights: 26 reversible cycles with 624 h were operated by a flat-tube SOC. The CO2 conversion rate reached 45.7% at −200 mA/cm 2 and 1.07 V. The energy conversion efficiency was 81.42% in electrolysis mode. The degradation rate in electrolysis is two times higher than that in discharging. Abstract: Solid oxide cells (SOCs) are promising for CO2 electrolysis. In this work, performance and stability of flat-tube SOCs during periodic cycles of CO2 electrolysis and hydrogen fuel discharge were studied. The cell underwent 26 reversible cycles of operation for 624 h. When the cell was electrolyzed with a current density of −200 mA/cm 2 at 1.07 V, the CO yield was 205.79 sccm and the CO2 conversion rate reached 45.7%. When the cell was operated in electrolysis mode, the degradation rate was 0.74 mV/h. Excluding the air heat consumption, the energy conversion efficiency was 81.42%; when the cell was operated at 0.6 slm hydrogen and +200 mA/cm 2, the degradation rate was 0.385 mV/h. Compared with long-term constant current electrolysis, the alternate operation of charge and discharge used in this study is more typical of the actual application conditions.